Trabalhando habilidades da BNCC através de métodos de cálculo de raízes quadradas aproximadas no Ensino Fundamental - Silva, Alex Roberto da (2023)
In this study, an approach will be presented to explore and develop the skills outlined in the BNCC through the topic of approximate square roots. Despite being present in various concepts and problem-solving situations in Elementary Education, this theme is scarcely addressed, both in teaching and in textbooks. Therefore, this research will underscore the significance of this topic and propose the introduction of some methods for approximating square roots, along with their respective analyses and error estimates. Furthermore, the implementation of these methods in the classroom will be suggested through a didactic sequence. In this manner, it is anticipated that this work can foster students’ creativity and logical reasoning within the realm of algebraic and computational thinking. This will be achieved through comprehension and proficiency in working with mathematical formulas, providing students with an additional tool to approach other concepts, such as the positioning of irrational numbers on the real number line and geometry problems.